Graphite reinforced high-entropy alloy and preparation method thereof
By adding an appropriate amount of graphite powder to the high-entropy alloy and adopting a specific preparation process, the problem of optimization of performance of high-entropy alloys is solved, and the comprehensive performance improvement of hardness improvement, friction coefficient reduction, compressive strength enhancement and wear rate reduction is achieved.
Patent Information
- Application Number
- CN202510037357.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the performance of high-entropy alloys needs to be improved and optimized to meet the needs of industrial fields such as marine engineering, aerospace, minerals, and chemicals.
Graphite-enhancing high-entropy alloy composites are prepared by mixing graphite powder with CoCrNiCuFe high-entropy alloy powder in a specific molar ratio, and using ball milling and discharge plasma sintering technology to control the mass percentage of graphite powder between 0 and 5%, especially at 0.15 wt.% to achieve the best effect.
The performance optimization of high-entropy alloys is achieved, including improving Vickers hardness, reducing friction coefficient, enhancing compressive strength and reducing wear rate, and graphite produces solid solution strengthening and fine crystal strengthening effects on high-entropy alloys.
Smart Images

Figure CN119876731A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal-based composite materials, and in particular relates to a graphite-reinforced high-entropy alloy and a preparation method thereof. Background Art
[0002] High entropy alloys prepared with Co, Cr, Ni, Fe, and Cu metal powders have excellent properties such as high strength, corrosion resistance, oxidation resistance, and wear resistance. They have broad application prospects in industrial fields such as shipbuilding and marine engineering, aerospace, mining, and chemical industries. In order to further improve and optimize the performance of high entropy alloys, carbon-containing CoCrNiCuFe high entropy alloy composites were prepared using graphite as raw material by mechanical alloying and spark plasma sintering technology, and the effects of carbon content, process parameters, and their organization and properties were explored. Summary of the invention
[0003] In view of this, the technical problem to be solved by the present invention is to provide a graphite-reinforced high-entropy alloy and a preparation method thereof, which solves the problem in the prior art of needing to improve and optimize the performance of high-entropy alloys.
[0004] In order to solve the above technical problems, the present invention discloses a graphite-reinforced high-entropy alloy, which is composited into C-CoCrNiCuFe with high-entropy alloy powder as a base phase and graphite powder as a reinforcement phase; the raw materials of the high-entropy alloy powder CoCrNiCuFe include Co powder, Cr powder, Ni powder, Fe powder and Cu powder, the molar ratio of Co, Cr, Ni, Fe and Cu is 1:1:1:1:1, and the mass percentage of graphite powder C is 0-5%.
[0005] Furthermore, when the C content of the graphite powder is 0.15 wt.%, the Vickers hardness of the C-CoCrNiCuFe high entropy alloy composite material reaches a maximum of 490.4 HV 0.5 .
[0006] Furthermore, when the C content of the above-mentioned graphite powder is 0.15 wt.%, the friction coefficient reaches a minimum of 0.51. Compared with the CoCrNiCuFe high entropy alloy, the friction coefficient of the 0.15 wt.% C-CoCrNiCuFe high entropy alloy composite material decreases by 11 to 13%.
[0007] A method for preparing a graphite-enhanced high entropy alloy, comprising the following steps: S1. Preparation of high entropy alloy powder: CoCrNiCuFe high entropy alloy is mainly used. In a glove box filled with argon, the metal powders are mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC composite material ball mill. The ball-to-material mass ratio is 10:1-20:1, the rotation speed is 300-600 r / min, the ball milling time is 20-50 h, and the machine is stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed after stopping every 10 h, and the ball milling is continued to obtain CoCrNiCuFe powder with a fineness of less than 150 nm. S2. Preparation of graphite powder: The graphite powder is ball-milled, with a ball-to-material mass ratio of 10:1 to 20:1, a rotation speed of 250 to 400 r / min, a ball-milling time of 10 to 40 h, and a 30-min stop for heat dissipation every 5 h to obtain a graphite powder with a particle size of 150 nm or less; S3, mixing: in a glove box filled with argon, weigh 5-30wt.% of the high entropy alloy powder prepared in step S1, add it to the graphite powder prepared in step S2, and then ball mill the mixture, the ball:material mass ratio is 5:1-10:1, the rotation speed is 200-350 r / min, the ball milling time is 2-5 h, and the mill is stopped for 10 min every 1 h for heat dissipation; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 10-30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 30-50 MPa, the sintering temperature is 950-1050 ℃, the heating rate is 50-100 ℃ / min, and the holding time is 5-15 min; then the temperature is reduced and the pressure is released to obtain a graphite composite material combined with a high entropy alloy.
[0008] Furthermore, the optimal sintering temperature of the above-mentioned 0.07-5wt.% C-CoCrNiCuFe high entropy alloy composite material is 1000°C.
[0009] Compared with the prior art, the present application can obtain the following technical effects: In the present invention, 0.15 wt.% of graphite has the best strengthening effect on CoCrNiCuFe high entropy alloy. When the carbon-containing strengthening phase is added to the CoCrNiCuFe high entropy alloy, the CoCrNiCuFe high entropy alloy maintains a relatively complete FCC solid solution structure. The density, compactness, Vickers hardness, compressive strength, friction coefficient and wear rate of the composite material are 7.89 g / cm3, 95.0%, 490.4 HV0.5, 1775 MPa, 0.51 and 2×10-5 mm3 / (N·m), respectively. Graphite produces solid solution strengthening and fine grain strengthening effects on CoCrNiCuFe high entropy alloy.
[0010] Of course, any product implementing this application does not necessarily need to achieve all of the technical effects described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings: Figure 1 is the surface SEM image of 0.1 wt.% C-CoCrNiCuFe high entropy alloy composite; Figure 2 is the surface SEM image of 0.15 wt.% C-CoCrNiCuFe high entropy alloy composite; Figure 3 is the surface SEM image of 0.3 wt.% C-CoCrNiCuFe high entropy alloy composite; Figure 4 These are the SEM and EDS point analysis images of the fracture of 0.15 wt.% C-CoCrNiCuFe high entropy alloy composite material. DETAILED DESCRIPTION
[0012] The following will describe the implementation methods of the present application in detail with the help of accompanying drawings and examples, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0013] Please refer to Figures 1 to 4 , Figure 1 is the surface SEM image of 0.1 wt.% C-CoCrNiCuFe high entropy alloy composite; Figure 2 is the surface SEM image of 0.15 wt.% C-CoCrNiCuFe high entropy alloy composite; Figure 3 is the surface SEM image of 0.3 wt.% C-CoCrNiCuFe high entropy alloy composite; Figure 4 These are the SEM and EDS point analysis images of the fracture of 0.15 wt.% C-CoCrNiCuFe high entropy alloy composite material.
[0014] A graphite-reinforced high-entropy alloy is composited into C-CoCrNiCuFe with high-entropy alloy powder as a base phase and graphite powder as a reinforcement phase; raw materials of the high-entropy alloy powder CoCrNiCuFe include Co powder, Cr powder, Ni powder, Fe powder and Cu powder, the molar ratio of Co, Cr, Ni, Fe and Cu is 1:1:1:1:1, and the mass percentage of graphite powder C is 0-5%.
[0015] 1. Estimation of the theoretical carbon dissolution capacity of CoCrNiCuFe high entropy alloy Carbon content is the most important factor affecting carbon-containing CoCrNiCuFe high entropy alloy composites. How to determine the theoretical carbon content of the preliminary test is a key factor. Through calculations and literature review, it is known that there is currently no accurate method to obtain the carbon capacity in CoCrNiCuFe high entropy alloys. Through the analysis of the physical phase of CoCrNiCuFe high entropy alloys, it is concluded that CoCrNiCuFe high entropy alloys are face-centered cubic single-phase solid solutions with a stable crystal structure. In order to obtain the theoretical carbon solubility, this study calculates the size of the interstitial position in the FCC structure of the high entropy alloy, and then estimates the solubility of carbon atoms by using the method of carbon atom filling.
[0016] According to the content of atomic stacking and gaps in the solid structure chapter of "Basics of Materials Science", the gap sizes of tetrahedron and octahedron in FCC structure are calculated. The atomic close-packed plane and close-packed direction of face-centered cubic are {111} <110> Through the analysis of the crystal structure gap model, we can know the type, number and size of gaps in the face-centered cubic crystal structure, as shown in Table 1-1. The XRD pattern of CoCrNiCuFe high entropy alloy is used to calculate the lattice constant of the experimentally prepared sample using Cell Refinement in jade software: a=b=c=3.595 Å (here, the error between the lattice constants a, b, and c caused by the lattice distortion of the high entropy alloy is ignored).
[0017]
[0018] The metal elements in the CoCrNiCuFe high entropy alloy are in equal molar ratios. Taking a face-centered cubic unit cell structure as an example, according to formula (1-1): (1-1) Calculations show that: rA=0.127 nm, rB1=0.029 nm (tetrahedral gap), rB2=0.053 nm (octahedral gap).
[0019] According to the data, the radius of carbon atoms is 0.077 nm>rB2, which shows that the radius of carbon atoms is larger than the maximum atomic radius that can enter the octahedral gap. Therefore, it is impossible for carbon atoms to fill all equivalent gap positions. Therefore, it is assumed here that a unit cell contains one carbon atom and a unit cell contains 4 metal atoms. The average relative molecular mass of the five-component atoms is: M=57.78 g / mol, and the mass fraction of carbon in this state is: WC=12 / (12+4×57.78)=4.9wt.%.
[0020] The 4.9 wt.% obtained here is an expanded amount. The actual upper limit is lower than this value, and its lower limit can be infinitely close to 0.
[0021] 2. SEM surface micromorphology analysis Figure 1 This is the surface SEM image of 0.1 wt.% C-CoCrNiCuFe high entropy alloy composite material. In the 0.1 wt.% C-CoCrNiCuFe high entropy alloy composite material, the mass fraction of graphite C added is 0.1%. It can be seen that the surface morphology is relatively uniform, but there are some black spots, which are due to the aggregation of some elements. Figure 3 (a), (b), (c), and (d) are the surface morphologies of 0.1 wt.% C-CoCrNiCuFe high entropy alloy composites at magnifications of 1000, 3000, 5000, and 10000 times, respectively. Figure 3 In (a), scattered black spots can be clearly observed. In order to further observe the difference between the black area and other parts, the morphology is gradually enlarged. With the increase of magnification, the morphology of the black area gradually becomes clear. When it is magnified to 10,000 times, it is found that the organizational morphology of the black area is basically the same as the surrounding morphology except for the color, and the continuity of the contact part is relatively good. This is believed to be the result of different element content ratios in different areas.
[0022] In 0.15 wt.%C-CoCrNiCuFe high entropy alloy composites, such as Figure 2 The mass fraction of the added graphite C content is 0.15%. It can be seen that the surface morphology of the material is very complete and uniform, without particularly obvious defects and partitions. Figure 2 (a), (b), (c), and (d) are the surface morphology images of 0.15 wt.% C-CoCrNiCuFe high entropy alloy composites at 1000, 3000, 5000, and 10000 times magnification, respectively. Through gradual magnification, slight black matter appears on the surface, but it is evenly distributed on the surface of the material. Compared with the C content of 0.1 wt.%, the surface of 0.15 wt.% C-CoCrNiCuFe high entropy alloy composite is more uniform and fine, and the dark area is more evenly distributed, but the high-magnification micro-area has a relatively uneven organization. For high-entropy alloys, the uniform distribution of components is conducive to the improvement of comprehensive performance and can inhibit the formation of carbides to a certain extent.
[0023] In 0.3 wt.%C-CoCrNiCuFe high entropy alloy composites, such as Figure 3The mass fraction of the added graphite C content is 0.3 wt.%. It can be seen that the surface morphology of the material is relatively uniform, without particularly obvious defects and zoning. However, due to the increase in C content, the C and carbide content in the material increases, the black area increases significantly, and the Cr-rich area increases. The Cr element easily reacts with the C element to form carbides, and the surface structure of the material becomes coarser. Figure 3 (a), (b), (c), and (d) are the surface morphology images of 0.3wt.% C-CoCrNiCuFe high entropy alloy composites at 1000, 3000, 5000, and 10000 times magnification, respectively. In the gradually higher magnification images, the surface composition and organization distribution of the composite material become uneven, the dark areas gather, and the light areas become larger.
[0024] Figure 4 The SEM and EDS point analysis images of the fracture of 0.15 wt.% C-CoCrNiCuFe high entropy alloy composite material are shown in Figure 2. The area containing the strip-shaped material is selected for point analysis scanning to determine the element composition differences of different morphologies, such as Figure 4 6 positions in .
[0025] Table 1-2 is Figure 4 From the EDS point analysis element scanning results, it can be found that the C content in point 2, 5, and 6 is significantly higher than that in other areas, and the content of other elements is relatively low, indicating that the strip area is graphite, which is consistent with the surface scanning analysis and fracture surface analysis. The C content in point 1 is relatively low, and the ratio of other elements is closest to 1:1:1:1:1, and the content of Cr and Fe elements is relatively high; the C content and Cr content in point 2, 3, 4, and 5 are relatively high, combined with XRD phase analysis, indicating the presence of C and Cr3C2; the C content in point 6 is relatively high, and the atomic ratios of other elements are close to equal ratios, the Fe element is slightly higher, and Fe2C exists.
[0026]
[0027] Comprehensive analysis of the fracture and surface scanning results shows that the existence of C in the composite material is uniform. The slight morphological differences and different organizational performances may be due to the fact that the surface C is slightly worn during the rough grinding, fine grinding, polishing and other processes when the sample is processed on the plane, resulting in loss, while the C at the fracture is relatively intact. Comparing the plane and fracture scanning results, it is found that both explain the influence of C on the organizational morphology of the composite material from different aspects. The addition of graphite enters the crystals and grain boundaries of the high entropy alloy, producing solid solution strengthening and fine grain strengthening effects, proving that graphite has a good strengthening effect on CoCrNiCuFe high entropy alloy.
[0028] Density analysis According to the sintering temperature pre-experiment, the addition of C can increase the sintering temperature of CoCrNiCuFe high entropy alloy, and the sintering temperature is 1100 ℃ when the C content exceeds 0.9 wt.%. It can be found that with the increase of C content, the density of 0.9-5 wt.%C-CoCrNiCuFe high entropy alloy composite material gradually decreases. This is because the relative atomic mass of C atoms is relatively low. When C is added in excess, part of C enters the crystal to form a solid solution, and part of it will exist in the grain boundary in the form of a single substance, and a trace amount of carbide will be generated. The solid-solution C element also causes lattice distortion. Graphite attached to the grain boundary can hinder grain growth and cause a slight change in the volume of the CoCrNiCuFe high entropy alloy. Therefore, the addition of C will reduce the actual density of the high entropy alloy. The density of 0.9-5 wt.%C-CoCrNiCuFe high entropy alloy composites does not change much with the change of C content, and fluctuates around 93%. This is because the theoretical density of 0.9-5 wt.%C-CoCrNiCuFe high entropy alloy composites is obtained by multiplying the theoretical density of each element by the sum of their respective volume fractions. The theoretical density of graphite is 1.8 g / cm3. The addition of C accounts for a lower volume ratio, which reduces the overall theoretical density. Therefore, with the increase of C content, both the theoretical density and actual density of 0.9-5wt.%C-CoCrNiCuFe high entropy alloy composites decrease. According to the degree of reduction of the two densities, the density will fluctuate relatively, but it is generally stable at around 93%. The density at this time is relatively good for high entropy alloys, indicating that the densification effect of spark plasma sintering is better.
[0029] It can be found that at the sintering temperature of 1000 ℃, when the C content is lower than 0.9 wt.%, except for the pure high entropy alloy matrix, the density and compactness of the 0.07-0.9 wt.%C-CoCrNiCuFe high entropy alloy composite material first increase and then decrease with the increase of C content, reaching the maximum when the C content is 0.15 wt.%, with a density of 7.89 g / cm3 and a compactness of 95.0%. This is because when the C content is 0.15 wt.%, the solid solution strengthening and grain refinement strengthening effects of C in the CoCrNiCuFe high entropy alloy reach near the limit; when the C content is higher than 0.15 wt.%, there will be too much insoluble C and carbides, which will reduce the actual density of the high entropy alloy; and when the C content is lower than 0.15wt.%, the strengthening effect of C is low, but it also deepens the degree of lattice distortion. When the effect of C grain refinement strengthening is not enough to balance the effect of lattice distortion caused by solid solution, the actual density of the high entropy alloy will be reduced.
[0030] Hardness analysis When the C content exceeds 0.9 wt.%, the Vickers hardness of the composite material gradually decreases with the increase of C content. This is because the strengthening effect of C on CoCrNiCuFe high entropy alloy is limited. When the interstitial relative position of the face-centered cubic structure of CoCrNiCuFe is filled and the graphite effect at the grain boundary is saturated, the extra C will form insoluble C and carbides. At this time, the effect of C solid solution and fine grain strengthening is far lower than the destructive effect caused by a large amount of insoluble C and carbides, making the hardness of the composite material lower than that of the high entropy alloy. Therefore, it is necessary to reduce the C content. With the increase of C content, the Vickers hardness of the composite material first increases and then decreases, as shown in Table 1-3. When the C content is 0.15 wt.%, the Vickers hardness reaches a maximum of 490.4HV0.5, which is 22.6% higher than that of the high entropy alloy matrix. According to the literature, the Vickers hardness of general carbon-containing high entropy alloys is 200-600 HV, which varies with the different forms of carbon. When the C content is lower than 0.9 wt.%, as the C content increases, the C added to CoCrNiCuFe gradually enters the gaps and grain boundaries to form solid solution and fine grain strengthening, and the precipitated insoluble C and carbides are less; when the C content reaches 0.15 wt.%, the strengthening effect reaches near the limit; the C content continues to increase, and the C in CoCrNiCuFe reaches saturation. The excess C will exist in the composite material in the form of a single substance or carbide. Combined with the SEM and EDS images, it is found that the insoluble C is unevenly distributed in the material, which has a negative impact on the material. The formation of carbides, which precipitate between grains, can play a role in precipitation strengthening. However, through elemental composition analysis, it is found that the high entropy alloy component composition in different regions of the material is unevenly distributed, especially the Cr and Fe elements will have a large gap in atomic percentage with other elements. This is due to the generation of Cr3C2 and Fe2C, which will lead to a decrease in material performance.
[0031]
[0032] Friction and wear performance analysis As the C content increases, the friction coefficient of the composite material decreases first and then increases. When the C content is 0.15 wt.%, the friction coefficient reaches a minimum of 0.51. Compared with the CoCrNiCuFe high entropy alloy, the friction coefficient of the 0.15 wt.% C-CoCrNiCuFe high entropy alloy composite material decreases by about 12%. According to the literature, the friction coefficient of the five-element high entropy alloy containing elements such as Co, Cr, Ni, and Fe is generally around 0.65, and the friction coefficient of the CoCrNiCuFe high entropy alloy strengthened by C is generally between 0.2-0.6. As we all know, graphite has a layered structure, and its addition can reduce the friction coefficient of the composite material and improve the tribological properties. And through observation, it is found that the wear rate and friction coefficient of the composite material have similar trends, indicating that the wear of the material is affected by graphite lubrication and strengthening. When the C content is 0.15 wt.%, the wear rate reaches the lowest of 2.0×10-5 mm3 / (N·m), which is about 96% lower than that of pure CoCrNiCuFe high entropy alloy, and the wear rate of composite materials with other C contents is much lower than that of pure high entropy alloy. Therefore, this shows that the addition of graphite can greatly reduce the wear rate of CoCrNiCuFe high entropy alloy.
[0033] A graphite-reinforced high-entropy alloy is composited into C-CoCrNiCuFe with high-entropy alloy powder as a base phase and graphite powder as a reinforcement phase; raw materials of the high-entropy alloy powder CoCrNiCuFe include Co powder, Cr powder, Ni powder, Fe powder and Cu powder, the molar ratio of Co, Cr, Ni, Fe and Cu is 1:1:1:1:1, and the mass percentage of graphite powder C is 0-5%.
[0034] A method for preparing a graphite-enhanced high entropy alloy, comprising the following steps: S1. Preparation of high entropy alloy powder: CoCrNiCuFe high entropy alloy is mainly used. In a glove box filled with argon, the metal powders are mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC composite material ball mill. The ball-to-material mass ratio is 10:1-20:1, the rotation speed is 300-600 r / min, the ball milling time is 20-50 h, and the machine is stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed after stopping every 10 h, and the ball milling is continued to obtain CoCrNiCuFe powder with a fineness of less than 150 nm. S2. Preparation of graphite powder: The graphite powder is ball-milled, with a ball-to-material mass ratio of 10:1 to 20:1, a rotation speed of 250 to 400 r / min, a ball-milling time of 10 to 40 h, and a 30-min stop for heat dissipation every 5 h to obtain a graphite powder with a particle size of 150 nm or less; S3, mixing: in a glove box filled with argon, weigh 5-30wt.% of the high entropy alloy powder prepared in step S1, add it to the graphite powder prepared in step S2, and then ball mill the mixture, the ball:material mass ratio is 5:1-10:1, the rotation speed is 200-350 r / min, the ball milling time is 2-5 h, and the mill is stopped for 10 min every 1 h for heat dissipation; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 10-30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 30-50 MPa, the sintering temperature is 950-1050 ℃, the heating rate is 50-100 ℃ / min, and the holding time is 5-15 min; then the temperature is reduced and the pressure is released to obtain a graphite composite material combined with a high entropy alloy.
[0035]
[0036] As shown in the table above, when the graphite content is less than 1 wt.%, as the C content increases, the density, compactness and hardness of the composite material increase and then decrease, and the friction coefficient and wear rate decrease first and then increase, and both reach the best when the C content is 0.15 wt.%. The addition of graphite can produce solid solution and fine grain strengthening effects on CoCrNiCuFe high entropy alloy, thereby improving the performance of the composite material, but when the graphite content exceeds 0.15 wt.%, insoluble carbon and carbides will be produced, destroying the microstructure of CoCrNiCuFe high entropy alloy. Considering comprehensively, the comprehensive performance of 0.15 wt.%C-CoCrNiCuFe high entropy alloy composite material is the best. When the sintering temperature is 1000 ℃, the comprehensive performance of 0.15 wt.%C-CoCrNiCuFe high entropy alloy composite material is the best. Too high sintering temperature will lead to the decomposition of high entropy alloy. As the sintering pressure increases, the composite material gradually becomes dense, but when the pressure exceeds 40 MPa, the uniformity of the material composition will be affected. The increase of heating rate can prevent excessive growth of grains. When the heating rate exceeds 70 ℃ / min, it will affect the uniformity of material composition. Too short holding time is not conducive to the formation of high entropy alloy solid solution. When the holding time exceeds 10 min, it is easy to cause grain growth. Factors such as mixing and pre-pressing process have little effect on the composite material.
[0037] In summary, 0.15 wt.% of graphite in the present invention has the best strengthening effect on CoCrNiCuFe high entropy alloy. When the carbon-containing strengthening phase is added to the CoCrNiCuFe high entropy alloy, the CoCrNiCuFe high entropy alloy maintains a relatively complete FCC solid solution structure. The density, compactness, Vickers hardness, compressive strength, friction coefficient and wear rate of the composite material are 7.89 g / cm3, 95.0%, 490.4 HV0.5, 1775 MPa, 0.51 and 2×10-5 mm3 / (N·m), respectively. Graphite produces solid solution strengthening and fine grain strengthening effects on CoCrNiCuFe high entropy alloy.
[0038] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and variations made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.
Claims
1. A graphite-enhanced high entropy alloy, characterized in that: C-CoCrNiCuFe is composited with high entropy alloy powder as a base phase and graphite powder as a reinforcement phase; raw materials of the high entropy alloy powder CoCrNiCuFe include Co powder, Cr powder, Ni powder, Fe powder and Cu powder, the molar ratio of Co, Cr, Ni, Fe and Cu is 1:1:1:1:1, and the mass percentage of graphite powder C is 0-5%.
2. The graphite-enhanced high entropy alloy according to claim 1, characterized in that: When the graphite powder C content is 0.15 wt.%, the Vickers hardness of the C-CoCrNiCuFe high entropy alloy composite material reaches a maximum of 490.4 HV 0.5 .
3. The graphite enhanced high entropy alloy according to claim 1, characterized in that: When the graphite powder C content is 0.15 wt.%, the friction coefficient reaches the lowest of 0.
51. Compared with the CoCrNiCuFe high entropy alloy, the friction coefficient of 0.15 wt.% C-CoCrNiCuFe high entropy alloy composite material decreases by 11-13%.
4. A method for preparing the graphite enhanced high entropy alloy as claimed in claim 1, characterized in that: Here are the steps: S1. Preparation of high entropy alloy powder: CoCrNiCuFe high entropy alloy is mainly used. In a glove box filled with argon, the metal powders are mixed in a molar ratio of 1:1:1:1:1 and loaded into a WC composite material ball mill. The ball-to-material mass ratio is 10:1-20:1, the rotation speed is 300-600 r / min, the ball milling time is 20-50 h, and the machine is stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed after stopping every 10 h, and the ball milling is continued to obtain CoCrNiCuFe powder with a fineness of less than 150 nm. S2. Preparation of graphite powder: The graphite powder is ball-milled, with a ball-to-material mass ratio of 10:1 to 20:1, a rotation speed of 250 to 400 r / min, a ball-milling time of 10 to 40 h, and a 30-min stop for heat dissipation every 5 h to obtain a graphite powder with a particle size of 150 nm or less; S3, mixing: in a glove box filled with argon, weigh 5-30wt.% of the high entropy alloy powder prepared in step S1, add it to the graphite powder prepared in step S2, and then ball mill the mixture, the ball:material mass ratio is 5:1-10:1, the rotation speed is 200-350 r / min, the ball milling time is 2-5 h, and the mill is stopped for 10 min every 1 h for heat dissipation; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 10-30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 30-50 MPa, the sintering temperature is 950-1050 ℃, the heating rate is 50-100 ℃ / min, and the holding time is 5-15 min; then the temperature is reduced and the pressure is released to obtain a graphite composite material combined with a high entropy alloy.
5. The method for graphite-enhanced high entropy alloy according to claim 4, characterized in that: The optimal sintering temperature of 0.07~5wt.%C-CoCrNiCuFe high entropy alloy composites is 1000℃.